The Effect of Arctic Sea‐Ice Loss on Extratropical Cyclones - Stephanie Hay; Matthew D. K. Priestley; Hao Yu; Jennifer L. Catto; James A. Screen (Geophysical Research Letters)
Abstract Taking advantage of the Polar Amplification Model Intercomparison Project simulations and using a Lagrangian objective feature tracking algorithm, we determine the response of extratropical cyclones to sea‐ice loss and consequent weakening of the equator‐to‐pole near‐surface temperature gradient. The wintertime storm tracks are found to shift equatorward in the North Atlantic and over Europe, and eastward in the North Pacific. In both regions, cyclones become weaker and slower, particularly on the poleward flank of the storm tracks. On average, there are fewer individual cyclones in the extratropics each winter, they last longer, are weaker, and travel more slowly. These changes are greatest over the Arctic, but still statistically significant in midlatitudes despite being small compared to internal variability. Inter‐model spread in cyclone responses are not strongly correlated with that in Arctic warming or Arctic amplification. Little change in summertime cyclones is found.